Analysis of novel cardiac biomarkers in diagnosis of decompensated heart failure. (3rd October 2022) - Froehling, T; Mirna, M; Paar, V; Shomanova, Z; Van Almsick, V; J Motloch, L; Semo, D; Makowski, L; Rukosujew, A; Sindermann, J R; Reinecke, H; Lichtenauer, M; et al.
Abstract: Aims: Heart failure (HF) remains a major therapeutic and diagnostic challenge. In this study we aimed to analyze the predictive potential of four novel cardiovascular biomarkers – soluble urokinase-type plasminogen activator receptor (suPAR), vascular cell adhesion molecule (CAM-1), heart-type fatty acid binding Protein (H-FABP) and growth/differentiation factor 15 (GDF-15) in detecting cardiac decompensation in patients with HF. Methods: In total, 136 patients (40 decompensated HF, 96 compesated HF) were retrospectively enrolled and the serum biomarker concentrations of GDF-15, suPAR, H-FABP and CAM-1 were analyzed by Enzyme Linked Immunosorbent Assay (ELISA). Biomarker concentrations were correlated with clinical and biochemical parameters of enrolled patients, the predictive value for detecting cardiac decompensation was assessed by ROC-plots, as well as univariate and multivariate logistic regression analysis. Cut-offs for cardiac decompensation were calculated by means of the Youden index. Results: A significant increase in the levels of suPAR (1.6-fold change, p<0.0001), CAM-1 (1.6-fold change, p<0.0001), HFABP (2.2-fold change, p=0.0458) and GDF-15 (1.7-fold change, p=0.0009) was detected in all patients with decompensated HF compared to patients with compensated HF. In univariate logistic regression analysis, plasma concentrations of GDF-15, H-FABP, suPAR and CAM-1 were significantly associated with the risk for cardiac decompensation. For GDF-15, suPAR and CAM-1, this association remained significant even after correction for confounders in a multivariate logistic regression analysis. Additionally, AUCs (GDF-15: 0.759, 95% (0.683–0.866), suPAR: 0.838, 95% (0.750–0.926), CAM-1: 0.838, 95% (0.750–0.926)) and optimal cut-offs (GDF-15: 1404.8835 pg/ml, suPAR: 4774.027 pg/ml, CAM-1: 4.74027 ng/ml) of the biomarkers were calculated. Correlation analyses found clinical and biochemical parameters such as creatinine as well as inflammatory marker CRP to be significantly correlated with novel biomarkers (r>0.3, p<0.001. In conjunction with the results for the AUC of NTproBNP (AUC=0.785), suPAR (AUC=0.838) and CAM-1 (AUC=0.838 more accurately prediced cardiac decompensation in heart failure than NTproBNP (Figure 1). Conclusion: In conclusion, the investigated novel cardiovascular biomarkers could be a valuable tool to facilitate therapeutic decisions in patients with HF and suspicion of cardiac decompensation. Parameters such as renal function should be taken into account. Funding Acknowledgement: Type of funding sources: None.